ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA PADA MASA PANDEMI COVID-19 - Tumeal Duri; Roslian Lubis; Marzuki Ahmad (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
The aim of study is to know the students’ mathematics critical thinking ability on the topic of lines and sequences arithmetic in pandemic Covid-19 period at SMA Negeri 1Padang Bolak. The approach of the research used qualitative descriptive and data analysis technique includes data reduction, data presentation, and taking conclusion. Instrument of the research used test and semistructure interview. the result of the research shows the average of students’ mathematics critical thinking ability on the topic of lines and sequences arithmetic in SMA Negeri 1 Padang Bolak is 67.26 (enough category). Only 8 from 10 students are able to answer three question completely and the rest are able to answer one from three questions.